Evolution of Genome-Organizing Long Non-coding RNAs in Metazoans - Ramírez-Colmenero, América; Oktaba, Katarzyna; Fernandez-Valverde, Selene L. (Frontiers in Genetics, 2020)
Long non-coding RNAs (lncRNAs) have important regulatory functions across eukarya. It is now clear that many of these functions are related to gene expression regulation through their capacity to recruit epigenetic modifiers and establish chromatin interactions. Several lncRNAs have been recently shown to participate in modulating chromatin within the spatial organization of the genome in the three-dimensional space of the nucleus. The identification of lncRNA candidates is challenging, as it is their functional characterization. Conservation signatures of lncRNAs are different from those of protein-coding genes, making identifying lncRNAs under selection a difficult task, and the homology between lncRNAs may not be readily apparent. Here, we review the evidence for these higher-order genome organization functions of lncRNAs in animals and the evolutionary signatures they display.